Puffin the architect - Andrews, Kimberly (Kimberly Tethera) ([North Sydney, New South Wales] : Penguin Random House Australia, 2018)
Puffin is an architect who always exceeds her clients' expectations. That is, until she takes on the toughest clients ever - her own pufflings! Puffin takes her tricky new clients on an inspirational tour of her builds. Together they visit all kinds of cleverly designed spaces - Otter's floating home, Pig's toolshed on wheels, Painter Goose's light-filled studio and Platypus's cosy underground bakehouse. The pufflings are unimpressed. Her clients really are a challenge! Will Puffin come up with a puffling-perfect home design? This gorgeous story, with endearing animal characters, intriguing house designs, ingenious mechanisms and storage solutions to pore over on every page, will spark a brand new generation of architects, engineers and interior designers!
Illustrations on endpapers.
For children.
Keywords: Architecture, Domestic -- Pictorial works; Animals -- Pictorial works; Puffins -- Pictorial works; Children's stories; Picture books; Animals -- Juvenile fiction; Architecture, Domestic -- Juvenile fiction; Puffins -- Juvenile fiction; Puffins -- Pictorial works -- Juvenile fiction; Animals -- Pictorial works -- Juvenile fiction; Architecture, Domestic -- Pictorial works -- Juvenile fiction; Children's stories -- Pictorial works; Children's stories, New Zealand; Australian; Picture books